Chemical soil degradation in the area of the Głogów Copper Smelter protective forest = Degradacja ziemi na terenach byłej strefy ochronnej Huty Miedzi Głogów - Kostecki, Jakub; Greinert, Andrzej; Drab, Michał; Wasylewicz, Róża; Walczak, Barbara (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Earth surface is under the continous influence of the environmental factors ? both natural and anthropogenic. The significant impact on the environment can be noted in areas adjacent to the metal industry plants, in a consequence of pollutants emission, especially dusts containing the heavy metals, into the atmosphere. In the surroundings of Głogów Copper Smelter (GCS) elevated amounts of copper and lead has been noted.
Keywords: metale ciężkie; miedź; ołów; tereny poprzemysłowe; zanieczyszczenia gleb; heavy metals; cooper; lead; postindustrial areas; soil pollution